2008
DOI: 10.1007/s12262-008-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of the descent of PTH measured by intraoperative monitoring of intact-PTH in surgery for renal hyperparathyroidism

Abstract: Background In the setting of total parathyroidectomy and autotransplantation surgery (TPTxAS) treatment for secondary hyperparathyroidism (SHPT) we evaluated whether intraoperative parathyroid hormone (iPTH) monitoring is an useful tool as a reference for total parathyroid removal.Design Prospective open single value measurement effi cacy study of one intraoperative (i.o.) diagnostic monitoring method (iPTH ) on a cohort of surgical patients. Main outcome measures Serum levels of iPTH during surgery and predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(21 reference statements)
0
3
0
2
Order By: Relevance
“…There were some other studies that investigated the appropriate criteria, but also with very limited number of patients. 18 , 19 Thus, it was important to evaluate the efficacy of IO-iPTH monitoring in a larger study population.…”
Section: Discussionmentioning
confidence: 99%
“…There were some other studies that investigated the appropriate criteria, but also with very limited number of patients. 18 , 19 Thus, it was important to evaluate the efficacy of IO-iPTH monitoring in a larger study population.…”
Section: Discussionmentioning
confidence: 99%
“…Quality assessment of the included studies is shown in Table 3 . Three studies had a low risk of bias 43 , 46 , 54 , six a moderate risk of bias 21 , 40 , 45 , 49 , 50 , 53 and five a high risk of bias 42 , 44 , 47 , 51 , 52 . Three studies described the ioPTH and postoperative PTH assay in detail (e.g.…”
Section: Resultsmentioning
confidence: 98%
“…Sixteen studies were included after full-text review 21 , 40–53 . Since four studies included patients from two overlapping cohorts, the most recent cohorts, including the highest number of patients, were included 41 , 42 , 47 , 48 . A total of 14 papers were included for qualitative and quantitative analysis 21 , 40 , 42 , 44–47 , 49–53 .…”
Section: Resultsmentioning
confidence: 99%
“…Dėl šios hiperfunkcijos didėjanti PTH perprodukcija lemia pakitimus įvairiose žmogaus organų sistemose, ypač kauliniame audinyje, kuriame dažniausia pasireiškimo forma -osteodistrofija (1) (5). Nuo 1975 metų lėtinės inkstų patologijos sukeltam 2HPT gydyti naudojami keli chirurginiai metodai: subtotalinė paratiroidektomija (6), totalinė paratiroidektomija (toliau -TPT) su autotransplantacija (7) ir TPT be transplantacijos, kuri, kai kurių autorių nuomone, indikuotina dializuojamiems dėl lėtinės inkstų patologijos pacientams be inkstų transplantacijos perspektyvos ateityje (8).…”
Section: įVadasunclassified
“…Mokslinių tyrimų metu įrodyta, kad žmogus gali turėti nevienodą prieskydinių liaukų skaičių ir dažnai šių liaukų netipinę lokalizaciją. G. Akerstorm ir bendratyrėjai išnagri- Tyrimų rezultatai patvirtina, kad net apie 5 procentus atvejų dėl 2HPT operuojamiems pacientams gali būti paliktas ektopinis hormoniškai aktyvus paratiroidinis audinys (6), dažniausiai lemiantis tolimesnę PTH sekreciją ir rezidualinio antrinio hiperparatiroidizmo išsivystymą. Todėl svarbus yra iPTH matavimas, kurio adekvatus procentinis kritimas leidžia spręsti apie operacinio gydymo efektyvumą.…”
Section: Klinikinio Tyrimo Rezultataiunclassified